A TMS320C25-based telephone scrambler using fast-computable filter banks - Malvar, Henrique S.; Malvar, Henrique S. (International Conference on Signal Processing Applications and Technology, 1992)
In this work we describe the hardware architecture and the signal processing algorithm of a secure telephone which can be used over the public switched network. Using time-varying frequency-domain scrambling, a high level of security can be achieved, with no residual intelligibility. By means of the DFT filter banks implemented by the FFT and polyphase networks, all the signal processing for a full duplex conversation can be performed with a single TMS320C25 digital signal processor. The complete scrambler fits inside a standard telephone set unit.